2020
DOI: 10.1186/s12872-020-01596-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes in ischemic cardiomyopathy by gene expression omnibus database

Abstract: Background Ischemic cardiomyopathy (ICM) is one of the most usual causes of death worldwide. This study aimed to find the candidate gene for ICM. Methods We studied differentially expressed genes (DEGs) in ICM compared to healthy control. According to these DEGs, we carried out the functional annotation, protein-protein interaction (PPI) network and transcriptional regulatory network constructions. The expression of selected candidate genes were confirmed using a published dataset and Quantitative real time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
0
14
0
5
Order By: Relevance
“…Recently, the development of second-generation sequencing technologies, such as targeted gene sequencing, whole exon sequencing (WES) and whole genome sequencing appeared, these technologies can help to identify more HCM patients and discover more gene mutations. Integrated microarrays analysis from different data sets will obtain genome-wide expression pro ling with more samples which will increase the statistical power than an individual microarray [28]. Screening DEGs and biological pathways that are abnormally expressed in the pathogenesis of HCM through bioinformatics analysis would shed light on the diagnosis and treatment of HCM [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of second-generation sequencing technologies, such as targeted gene sequencing, whole exon sequencing (WES) and whole genome sequencing appeared, these technologies can help to identify more HCM patients and discover more gene mutations. Integrated microarrays analysis from different data sets will obtain genome-wide expression pro ling with more samples which will increase the statistical power than an individual microarray [28]. Screening DEGs and biological pathways that are abnormally expressed in the pathogenesis of HCM through bioinformatics analysis would shed light on the diagnosis and treatment of HCM [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the bone marrow, the levels of ВВЕДЕНИЕ Ишемическая кардиомиопатия (ИКМП) является осложненной формой хронической ишемической болезни сердца (ИБС) и служит одной из наиболее частых причин смертности во всем мире от сердечно-сосудистых заболеваний [1]. ИКМП характеризуется дилатацией камер сердца, гипертрофией (преимущественно левого желудочка) и снижением насосной функции сердца с формированием хронической сердечной недостаточности [2]. Считается, что в основе развития ИКМП лежит нарушение сократительной функции миокарда вследствие коронарной микрососудистой дисфункции, которая является триггером распространенной ишемии и гибернации миокарда, некроза и апоптоза кардиомиоцитов с последующим фиброзированием и ремоделированием желудочков [1,2].…”
Section: Methodsunclassified
“…Accumulated evidence demonstrates that numerous fetal and immediate-early genes present deregulation in ICM ( Dang et al, 2020 ). However, genetic causes and molecular mechanisms underlying ICM progression remain partially clarified ( Suffee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that gene signatures exert critical roles in diverse diseases that depend on the leapfrog advance of sequencing technologies ( Li et al, 2020 ). For instance, Dang et al proposed deregulated genes in ICM and their upstream transcription factors ( Dang et al, 2020 ). Wang et al reported that transcriptome profile analyses uncovered PHLDA1 as a candidate molecular signature for ICM ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%